E-COMMERCE CONSULTING SERVICES: THE NEW MODEL - Savchuk, L. M.; Shkil, R. O. (Science and Transport Progress, 2007)
The theoretical aspects of electronic commerce and consulting are considered in this article, a new model of cooperation of participants of market of electronic commerce is offered, as it applies to providing of consulting services.